THE IMPACT OF CARBON TAX CALCULATION ON ENVIRONMENTAL ISSUES AND THE TARGET TOWARDS NET ZERO EMISSION IN COAL POWER PLTU - Samasta, Endruw (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
The background of this research is efforts to reduce carbon emissions by applying a cap & tax scheme to calculating carbon taxes and implementing other NEKs in Presidential Decree 98/2021. The research was carried out by simulating carbon tax calculations in accordance with 3 approaches, namely carbon tax , RPMK and the Minister of Energy and Mineral Resources. By using the data in the explanation of the 2021 Ministry of Finance webinar. In carrying out a carbon tax calculation simulation, a carbon tax trading mechanism was carried out first by obtaining an SIE/SPE, this mechanism was carried out before the carbon levy mechanism or carbon tax was implemented. In the implementation of the NEK Perpres 98/2021, before levies on carbon or imposition of carbon taxes, another mechanism is first carried out, namely carbon trading and performance-based payments, only then a carbon tax is collected, this mechanism is carried out as an effort to mitigate climate change and target towards the NZE.